Tomorrow today: organ-on-a-chip advances towards clinically relevant pharmaceutical and medical in vitro models. (February 2019) - Rothbauer, Mario; Rosser, Julie M; Zirath, Helene; Ertl, Peter
Graphical abstract: Highlights: Physiologically relevant organ models based on microfabrication and bioengineering. Recent progress on organ-on-a-chip systems simulating kidney, brain, lung and gut, as well as cancer in vitro models. Disease-on-a-chip models emulating thrombosis, lung trauma as well as cancer progression and therapeutic outcomes. Organ-on-a-chip systems for personalized medicine. Abstract : Organ-on-a-chip technology offers the potential to recapitulate human physiology by keeping human cells in a precisely controlled and artificial tissue-like microenvironment. The current and potential advantages of organs-on-chips over conventional cell cultures systems and animal models have captured the attention of scientists, clinicians and policymakers as well as advocacy groups in the past few years. Recent advances in tissue engineering and stem cell research are also aiding the development of clinically relevant chip-based organ and diseases models with organ level physiology for drug screening, biomedical research and personalized medicine. Here, the latest advances in organ-on-a-chip technology are reviewed and future clinical applications discussed.